Improvement of the grapevine gene pool on the basis of agrobiological and physio-biochemical assessment of new genotypes under the unstable moderate continental climate conditions of Southern Russia - V. S. Petrov; A. E. Mishko; D. M. Tsiku; A. A. Marmorshtein (Труды по прикладной ботанике, генетике и селекции)
Background. Development of table grape cultivars is currently aimed not only at higher vineyard productivity and grape quality but also at enhancing the adaptive potential of plants under the dynamic change in the climate conditions of Southern Russia. Increasing the share of modern Russian cultivars of table grapes will update and improve the assortment. The aim of this study was to evaluate new Russian hybrid grapevine forms according to their agrobiological, physiological and biochemical characteristics in the central agroecological zone of Krasnodar Territory.Materials and methods. Agrobiological characters were assessed using modern methods. Among physio-biochemical characters, the content of photosynthetic pigments was measured as well as the level of stress parameters under drought, such as the total water content in leaves and the content of malondialdehyde. Artificial drought was simulated to identify the most stress-resistant hybrid forms.Results. The highest values of fruitfulness coefficients k1 and k2 in the period of research were recorded for the Akello and Agat Dubovsky hybrid forms. Timoti and Agat Dubovsky had the maximum average yield for two years among the hybrid forms. The Gamlet, Kishmish Dubovsky, Agat Dubovsky and Timoti genotypes significantly exceeded the reference cultivar in the bunch weight. The Akello and Agat Dubovsky hybrids were identified for their physio-biochemical parameters: the highest content of chlorophyll in their leaves, high adaptive potential expressed in a low development level of secondary oxidative processes under stress, and the highest content of carotenoids.Conclusion. The obtained results evidenced that the Agat Dubovsky hybrid form could be identified as the most promising among the studied genotypes for cultivation in Southern Russia.